Product Innovation Strategy in Increasing the Competitiveness of MSMEs in the Digital Era - Muhammad Irfan; Agus Suyatno (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. However, in facing the digital era, MSMEs are required to continue to innovate in order to be able to compete in an increasingly competitive market. This study aims to analyze product innovation strategies that can be applied by MSMEs to increase their competitiveness in the digital era. The research method uses a descriptive qualitative approach with literature studies from various journals and relevant reports. The results of the study indicate that digital-based product innovation, utilization of information technology, and adaptation to market needs are key factors in strengthening the position of MSMEs. Strategic recommendations include digitalization training, improving product quality, and collaboration with digital platforms.